1993
DOI: 10.1177/002204269302300406
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Relationship between Self Esteem and Drug Use? Methodological and Statistical Limitations of the Research

Abstract: Although a causal connection between self-esteem and drug use might make intuitive sense, a critical evaluation of the research calls this relationship into question. The most fatal flaw in the “low self-esteem causes drug use” argument is the fact that only a very small proportion of the variance in drug use is associated with self-esteem across a variety of definitions of self-esteem. In addition, the literature is fraught with methodological and statistical problems that severely limit the conclusions that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 46 publications
3
24
0
5
Order By: Relevance
“…Crandall [42] lists more than 60 measures of self-esteem. The correlations between the various selfesteem measures "are sufficiently small to suggest that they are not all measuring the same construct" [43]. Many adolescent health researchers have used the Rosenberg Selfesteem Scale.…”
Section: Self-esteemmentioning
confidence: 99%
“…Crandall [42] lists more than 60 measures of self-esteem. The correlations between the various selfesteem measures "are sufficiently small to suggest that they are not all measuring the same construct" [43]. Many adolescent health researchers have used the Rosenberg Selfesteem Scale.…”
Section: Self-esteemmentioning
confidence: 99%
“…Moreover, it has been argued that adolescents with low selfesteem show a general tendency toward adjustment problems (DuBois & Hirsch, 2000;Kernis et al, 1998;Mizell, 1999) such as behavioral problems and low scholastic achievement (Flores-Fahs et al, 1997;Mone, Baker & Jeffries, 1995;Owens, 1994;Vega, Apospori, Gil, Zimmerman, & Warheit, 1996). Other studies, however, have revealed little or no relationship between self-esteem and behavioral problems (Jang & Thornberry, 1998;Schroeder, Laflin, & Weis, 1993).…”
Section: Internal and External Resources And Their Relation To Adjustmentioning
confidence: 99%
“…Numerosos autores sugieren que estas inconsistencias pueden atribuirse a la medición del autoconcepto como un constructo unidimensional o multidimensional (Cava, Murgui y Musitu, 2008;Musitu, Jiménez y Murgui, 2007;Swaim y Wayman, 2004). Sin embargo, es poco factible asumir que estas discrepancias en torno a la relación entre el autoconcepto y el consumo de sustancias se deban, únicamente, al tipo de instrumento utilizado para medir el autoconcepto (Schroeder, Laflin y Weis, 1993), puesto que, al revisar la literatura siguiendo este criterio, los resultados siguen siendo inconsistentes. Si bien, las medidas multidimensionales ofrecen mediciones más sensibles, concretas y ajustadas (García, Musitu y Veiga, 2006;Palacios y Zabala, 2007;Shavelson et al, 1976;Tomás y Oliver, 2004;Wylie, 1979) en comparación con las medidas globales e inespecíficas proporcionadas por los modelos unidimensionales (Braken, 1992;Fuentes, García, Gracia y Lila, 2011;García, Musitu, Riquelme y Riquelme, 2011;Shavelson et al, 1976), medidas que distorsionan la verdadera relación entre el autoconcepto y el consumo de sustancias (Swaim y Wayman, 2004).…”
Section: Introductionunclassified